The Role of Customer Satisfaction in Mediating the Influence of Online Sales Ethics on E-Commerce Repurchase Intention - Tazkiyah Sakinah; Laili Fadhila Banuwa; Nuzul Inas Nabila; Risda Marvinita (IPB University, 2026)
Public concerns about online shopping remain an important issue to address, given the rapid growth of business in today's digital age. A number of businesses tend to ignore ethics for short-term profits that can damage long-term relationships with consumers. Online seller ethics, known as Consumer Perception of Ethics of Online Retailers (CPEOR), covers several dimensions, namely security, non-deception, and fulfillment. In order to maintain customer loyalty, this study analyzes online sales ethics to support repurchase intention with customer satisfaction as a mediator. Data was collected through an online survey conducted on 409 e-commerce consumers who had made at least two purchases. The research hypothesis was tested using structural equation modeling partial least squares (SEM-PLS). Based on the analysis results, online sales ethics demonstrated by security and fulfillment have a significant effect on repurchase intention mediated by customer satisfaction. Meanwhile, non-deception directly influences repurchase intention even without being mediated by customer satisfaction. The results indicate that post-purchase experience and ethical business practices are important factors in fostering customer loyalty in digital businesses.